Peran Hukum Syariah dalam Pengelolaan Sumber Daya Alam - Eka Wahyu Kasih; Ruslaini Ruslaini (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study aims to analyze the role of Sharia law in natural resource management through a qualitative literature review, focusing on Sharia principles such as hifz al-nafs, hifz al-maal, and maslahah. The findings reveal that Sharia law provides a strong ethical framework for environmental management, emphasizing sustainability, ecosystem balance, and human religious responsibility toward nature. However, challenges in its implementation include a lack of public awareness and limited resources. The study recommends strengthening institutional capacity, community education, and stakeholder collaboration to support more sustainable natural resource management. With a comprehensive approach, Sharia law has the potential to serve as a model for environmental management that not only prioritizes worldly benefits but also spiritual harmony.